2007
DOI: 10.1140/epja/i2007-10432-4
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of high-energy particles in the electrostatic field of a homogeneously charged sphere and the effective momentum approximation

Abstract: The impact of the strongly attractive electromagnetic field of heavy nuclei on electrons in quasielastic (e, e ′ ) scattering is often accounted for by the effective momentum approximation. This method is a plane wave Born approximation which takes the twofold effect of the attractive nucleus on initial and final state electrons into account, namely the modification of the electron momentum in the vicinity of the nucleus, and the focusing of electrons towards the nuclear region leading to an enhancement of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The reason is twofold. Firstly, the energy of the final state electrons is relatively small, and the focusing effect becomes more important [51], such that the DWBA cross section becomes significantly larger than the EMA prediction. Secondly, the quasi-elastic peak is shifted towards smaller energy transfer, where the optical potential increasingly distorts the wave functions of the final state nucleons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason is twofold. Firstly, the energy of the final state electrons is relatively small, and the focusing effect becomes more important [51], such that the DWBA cross section becomes significantly larger than the EMA prediction. Secondly, the quasi-elastic peak is shifted towards smaller energy transfer, where the optical potential increasingly distorts the wave functions of the final state nucleons.…”
Section: Resultsmentioning
confidence: 99%
“…which interpolates between the non-relativistic and relativistic regime [51]. We additionally solved the Dirac equation for Dirac nucleons in the energydependent volume-central part of the optical potential used in this work for different energies, such that the amplitude of the eikonal phase corrected nucleon spinors could also be corrected by the corresponding energy-dependent amplitude modification.…”
Section: Eikonal Approximation For Nucleonsmentioning
confidence: 99%
See 1 more Smart Citation
“…where eff is the effective Coulomb potential. In a recent study using exact Dirac wave functions, it has been shown that an accurate approximation for the effective electron momenta is obtained by using the mean value of the Coulomb potential, eff = 4 (0)/5, where (0) = −3 /(2 ) corresponds to the electrostatic potential evaluated at the center of the nucleus [66,67].…”
Section: The Formalism For Neutrino-nucleus Cross Sections Calculationsmentioning
confidence: 99%
“…with V ef f = 4V C (0)/5 = −6Z f α/5R A [38,67]. These two approximations for the Coulomb correction were tested in the calculation of the inclusive cross section for neutrino scattering on 208 Pb [38].…”
Section: B Fermi Function and Effective Momentum Approximation (Ema)mentioning
confidence: 99%